MODAL INTELEKTUAL DAN KINERJA KEUANGAN : KEUNGGULAN BERSAING SEBAGAI VARIABEL INTERVENING - Muhammad Fahri Azmi; Yusralaini Yusralaini; Rofika Rofika (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to see the effect of VACA, VAHU, STVA, and VAIC on financial performance and competitive advantage, as well as the role of competitive advantage in mediating the effect of VACA, VAHU, STVA, and VAIC on financial performance. The population in this study is Islamic commercial banks registered with the financial services authority in 2016-2018. The sample of this research was selected by sampling criteria. Hypothesis testing used in this research is Structural Equation Modeling with Partial Least Square (SEM-PLS) approach and the statistical test tool used is WarpPLS 7.0. The results of this study indicate that VACA has a positive influence on financial performance, VAHU has a negative influence on financial performance while STVA and VAIC do not affect financial performance. Furthermore, this study found that VACA, STVA, and VAIC had a positive effect on competitive advantage and competitive advantage also has a positive effect on financial performance. This research also found that, while VAHU did not affect the competitive advantage that competitive advantage plays a role in mediating the effect of VACA and VAIC on financial performance, whereas competitive advantage does not mediate the effect of VAHU and STVA on financial performance.